First report of Anaplasma marginale and Anaplasma ovis in goats in Kelantan, Malaysia - Peng, T. L.; Yahya, S. N. C.; Mohamed, M.; Hamdan, R. H.; Shean, C. S.; Okene, I. A.; Sani, N. I. M.; Mohamad, N. F. A; Syazwan, S. A.; Onyiche, T. E. (Malaysian Society of Parasitology and Tropical Medicine, 2024)
Anaplasma species are obligate rickettsial intraerythrocytic pathogens that cause an important tick-borne disease of economic importance in livestock production in many countries. Anaplasma species have been detected from farm animals worldwide, there is a paucity of information on Anaplasma infections in goats from Malaysia. Thus, this study aimed to assess the infection rate and identify Anaplasma species and some selected risk factors in goats across selected districts in Kelantan, Malaysia. A total of 411 blood samples were collected from goats and analysed for Anaplasma species targeting the msp4 gene using conventional PCR and sequencing. The infection risk was determined by breed, age, management system and location. Our results indicate an overall infection rate of 30.9% for Anaplasma species detected. Interestingly, sequencing of selected amplicons revealed the presence of Anaplasma ovis and A. marginale. Data analysis revealed a marked statistically significant association between Anaplasma infection and some variables such as location (district), farm management system, breed, and age (P < 0.05). Specifically, goats raised on intensive management had the highest prevalence of 46.25% (37/80) compared to other management types. Also, with regards to district, goats raised in the coastal region had a higher prevalence of 39.23% (71/181) compared to those raised in inland region 24.35% (56/230). Regarding breed, goats that were of the pure breed had a higher prevalence of Anaplasma species infection 38.19% (97/254) compared to crossbreeds with a prevalence of 19.11% (30/157). Lastly, goats <1 year of age had the highest prevalence 42.71% (41/96) followed by those within 1-2 years 38.24% (52/136) while goats > 3 years had the least prevalence 18.99% (34/179). To the best of our knowledge, this is the first report of A. marginale and A. ovis in goats from northeastern Peninsular Malaysia. The infected goats were clinically healthy; this revealed the role of goats as a potential reservoir for A. marginale and the presence of A. ovis in goats in Malaysia. Continuous efforts towards tick control must be sustained to ensure high productive yield and reduced disease burden associated with TBPs of goats in the study area.